2020
DOI: 10.1038/s41598-020-72060-0
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven typology of asthma medication adherence using cluster analysis

Abstract: Asthma preventer medication non-adherence is strongly associated with poor asthma control. One-dimensional measures of adherence may ignore clinically important patterns of medication-taking behavior. We sought to construct a data-driven multi-dimensional typology of medication non-adherence in children with asthma. We analyzed data from an intervention study of electronic inhaler monitoring devices, comprising 211 patients yielding 35,161 person-days of data. Five adherence measures were extracted: the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…[34][35][36][37][38][39][40][41][42] Patient clustering refers to studies which subtype the asthma population using unsupervised learning algorithms. 43,44 See Table 2 for a summary of the papers.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34][35][36][37][38][39][40][41][42] Patient clustering refers to studies which subtype the asthma population using unsupervised learning algorithms. 43,44 See Table 2 for a summary of the papers.…”
Section: Search Resultsmentioning
confidence: 99%
“…Many methods and devices for monitoring different aspects of a person have been studied individually and in combination. Machine learning can be applied to breath monitoring, 37,41 sleep monitoring, 23,[34][35][36]38,39,42 cough and wheeze, 24,26,27,[29][30][31]36 lung function monitoring, 23,25,[33][34][35]38,40 adherence monitoring, 32,35,38,43 and environment monitoring. 39,40,44 However, studies had different outcome measures; hence, it is difficult to conduct a direct comparison between studies.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital inhalers can also be used to evaluate patterns of controller medication use, similarly to informing about SABA use patterns [ 64 ]. Previous studies using digital inhalers have identified different patterns of adherence, ranging from regular adherence and irregular adherence, to regular nonadherence and irregular nonadherence [ 64 , 65 ]. Clinicians will likely encounter patients who are non-adherent but controlled, though little has been published in this area.…”
Section: Methodsmentioning
confidence: 99%
“…For patients receiving r-hGH treatment (somatropin; Saizen ® , Merck Healthcare KGaA, Darmstadt, Germany), the easypod™ auto-injector device, in combination with easypod™ connect, allows automatic recording and real-time data transmission of the date, time, and dose injected [8] enabling healthcare professionals to monitor patient adherence and growth outcomes. Data from connected devices has also contributed to the development of machinelearning algorithms to predict adherence behavior in multiple therapy areas [9][10][11].…”
Section: Introductionmentioning
confidence: 99%